Kajian Arsitektur Vernakular dan Ramah Lingkungan pada Gedung Kampus Universitas Mataram - Teti Handayani; Rini Saptaningtyas; Zaedar Gazalba; Giska Pradana Ayu Putri Kamase; Jasmine Chanifah Uzdah Bachtiar; Ni Ketut Ayu Intan Putri Mentari Indriani (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2021)
In the last decade, the development of new buildings in Mataram University has shown a shift towards contemporary forms and materials which results a quite different facade / appearance from the existing buildings. The situation raises an awareness that if it is allowed to continue, Mataram University as one of the state universities in West Nusa Tenggara will lose its identity. This study aims to examine the characteristics of vernacular and environmentally friendly architecture that can be applied to Mataram University’s building and evaluate it in the old and new buildings. This study uses a qualitative method, by reviewing the literature and evaluating the building based on the criteria obtained. The library building represents the old building and the Fisipol building represents the new building as subjects studied. Data analysis was done by descriptively qualitatively. The results show that the library building and Fisipol meet the same criteria or vernacular architectural characteristics even though visually the buildings look different. However, the library building meets the criteria for environmentally friendly architecture compared to Fisipol building, which is a new building. This study is expected to increase research on vernacular architecture as the identity of new campuses in Indonesia. This research still has many shortcomings, therefore it requires more similar studies in the future.